2005
DOI: 10.1111/j.1440-1681.2005.04293.x
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac mitochondrial alterations induced by insulin deficiency and hyperinsulinaemia in rats: Targeting membrane homeostasis with trimetazidine

Abstract: The present study investigated the ability of trimetazidine (TMZ) to maintain cardiac mitochondrial function during the development of insulin deficiency and hyperinsulinaemia. The anti-ischaemic drug TMZ is known to increase phospholipid synthesis in cardiac membranes and to have a cardioprotective effect. Insulin deficiency was obtained by streptozotocin injection and hyperinsulinaemia was achieved via a fructose diet. Trimetazidine was incorporated into the diet (7.8 mg/day) and mitochondrial function was e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 45 publications
1
1
0
1
Order By: Relevance
“…These symptoms were all manifested in db/db mice, and ventricular mass did not differ among groups, consistent with the findings of a previous study[22]. The present study revealed that TMZ treatment was ineffective in treating these disease features, similar to earlier findings for STZ-induced mice[36]. Interestingly, however, blood glucose was decreased slightly in the group treated with high-dose TMZ.…”
Section: Discussionsupporting
confidence: 91%
“…These symptoms were all manifested in db/db mice, and ventricular mass did not differ among groups, consistent with the findings of a previous study[22]. The present study revealed that TMZ treatment was ineffective in treating these disease features, similar to earlier findings for STZ-induced mice[36]. Interestingly, however, blood glucose was decreased slightly in the group treated with high-dose TMZ.…”
Section: Discussionsupporting
confidence: 91%
“…Îñòàíí³ì ÷àñîì äåÿê³ äîñë³äíèêè çâåðòàþòü óâàãó òàêîae íà çì³íè aeèðíîêèñëîòíîãî ñêëàäó ìåìáðàí êàðä³îì³îöèò³â ïðè ñòðåïòîçîòîöèí³íäóêîâàíîìó ÖÄ [24,28]. Íà ö³é ìîäåë³ ä³àáåòó áóëî ïðîäåìîíñòðîâàíî çíà÷íå çíèaeåííÿ âì³ñòó ω-3 ïîë³íåíà-ñè÷åíèõ aeèðíèõ êèñëîò (ÏÍAEÊ) ó ôîñôîë³-ï³äàõ ñåðöÿ ³ ïîðóøåííÿ ñï³ââ³äíîøåííÿ ω-6/ω-3 ÏÍAEÊ ó á³ê çá³ëüøåííÿ ïåðøèõ.…”
Section: âñòóïunclassified
“…Streptozotocin‐induced insulin deficiency decreased mitochondrial affinity for ADP, the index of creatine kinase functional activity, and decreased n‐3 polyunsaturated fatty acids in rat heart mitochondria. When TMZ was added into the diet, the decrease in creatine kinase activity and the increase in n‐6/n‐3 ratio in mitochondrial membranes were partially prevented (Ovide‐Bordeaux et al 2005). This study supported that TMZ, although partially, maintained mitochondrial homeostasis in insulin deficiency.…”
Section: Pharmacological Effectsmentioning
confidence: 99%